»Luthera vöposlühnenje« – nova najdba iz evangeličanskega župnišča v Murski Soboti - Rágyanszki, György (Slavia Centralis, 2020)
"Luther’s examination" New find from Lutheran Parish in Murska SobotaAfter the First World War, Lutheran congregations established the Lutheran Deanery in Prekmurje. The board of the deanery protected the literary language of Prekmurje in their church publications. They explained literary language of Prekmurje as an independent Slavic language that has literary tradition since translation of the New Testament by Števan Küzmič (1711). I would like to introduce church literature in Prekmurje on Martin Luther. I will concentrate on a manuscript that includes the dispute between Martin Luther and Johann Eck in Worms. The text is a rewritten play of Otto Devrient’s (1838–1894) drama. The translator in Prekmurje did not use the original German version but a Hungarian dramatization by Gyula Porkoláb (1875–1913), who also worked as a Lutheran minister in Puconci.
Keywords: Evangeličanski koledar; Martin Luther; Gyula Porkoláb; Lutheran Deanery in Prekmurje; history of Slovene language